2019
DOI: 10.1038/s41386-019-0392-x
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia-like reduced sensorimotor gating in intact inbred and outbred rats is associated with decreased medial prefrontal cortex activity and volume

Abstract: Prepulse inhibition (PPI) of startle response is a measure of sensorimotor gating that is impaired in schizophrenia and in many other clinical conditions. Rat models using pharmacological or surgical strategies reveal that PPI is modulated by the cortico-striatalpallido-thalamic (CSPT) circuit. Here, we explore whether spontaneous variation in PPI in intact inbred and outbred rats is associated with functional and structural differences in the CSPT circuit. Inbred Roman High-(RHA) and Low-avoidance (RLA) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 71 publications
5
39
1
1
Order By: Relevance
“…In line with these strain-related differences in LI, we have shown in a series of studies that RHA rats display clear and consistent deficits of PPI of the acoustic startle response compared with RLAs (Del Rio et al, 2014; Oliveras et al, 2015, 2016, 2017; Río-Alamos et al, 2015; Río-Álamos et al, 2017a,b, 2019; Tapias-Espinosa et al, 2018, 2019) and that PPI deficits predict spatial working memory impairments (Oliveras et al, 2015). Altogether, the above mentioned cognitive and attentional profiles of RHA vs. RLA rats suggest that the former may represent a model of schizophrenia-relevant features.…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Comentioning
confidence: 55%
See 4 more Smart Citations
“…In line with these strain-related differences in LI, we have shown in a series of studies that RHA rats display clear and consistent deficits of PPI of the acoustic startle response compared with RLAs (Del Rio et al, 2014; Oliveras et al, 2015, 2016, 2017; Río-Alamos et al, 2015; Río-Álamos et al, 2017a,b, 2019; Tapias-Espinosa et al, 2018, 2019) and that PPI deficits predict spatial working memory impairments (Oliveras et al, 2015). Altogether, the above mentioned cognitive and attentional profiles of RHA vs. RLA rats suggest that the former may represent a model of schizophrenia-relevant features.…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Comentioning
confidence: 55%
“…Finally, it has recently been shown that, compared with their RLA counterparts, RHA rats exhibit significant reductions of the volumes of the mPFCx and HC [measured by means of magnetic resonance imaging (MRI)] as well as dramatically enlarged lateral ventricles (Río-Álamos et al, 2017a, 2019). In addition, PPI-elicited neural activity of the prefrontal cortex (as measured by c-fos activation) is lower in RHA than RLA rats (Tapias-Espinosa et al, 2019). These neuroanatomical and functional alterations are reminiscent of those observed in schizophrenic patients and provide further support to the contention that RHA rats may constitute a genetic model of schizophrenia-relevant features with face, construct, and predictive validity (reviewed by Río-Álamos et al, 2019).…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Comentioning
confidence: 99%
See 3 more Smart Citations